Topological Point Defects of Liquid Crystals in Quasi-Two-Dimensional Geometries - Harth, Kirsten; Stannarius, Ralf (Frontiers in Physics, 2020)
We review the interactions and dynamics of topological defects in liquid crystals (LCs) in quasi-twodimensional (2D) geometries. Such spatial restrictions can be realized in thin freely suspended smectic C films, in thin sandwich cells filled with nematic LCs, and under specific boundary conditions in LC shells embedded in aqueous solutions. Random defect patterns can be created by thermal quenching of the samples from lower ordered into higher ordered phases. On the other hand, well defined isolated defect configurations for the study of elementary interaction steps can be prepared by simple mechanical techniques. Observation by polarizing microscopy is straightforward. Spatial dimensions of the experimental systems as well as time scales are convenient for observation. The continuum theory of LCs is well developed so that in addition to the experimental characterization, an analytical or numerical description is feasible. From interactions and dynamic features observed in these LC systems, general conclusions on defect dynamics can be drawn.